Conceptualizing Indigenous Literatures - Khadka, Kul Bahadur (Journal of Development Review, 2022)
This article makes a quest for various concepts of Indigenous literatures. It deals with how the settler colonizers mainly in the context of North America traumatized the indigenous peoples and how the stories associated with them influence their generation now. It aims to disseminate the truth and beauty of Indigenous literatures and point out their equal quality and significance compared to the mainstream or non-indigenous literatures. The main ethos of indigenous literatures is relationship that evokes forgiveness, compassion and hope. Indigenous literatures remind the past and teach the present generations to struggle and prove themselves as good ancestors for their posterity. They speak for the wellbeing of humans and other-than-human beings. ndigenous literatures condemn isolation and fragmentation. They focus on interdependencies and mutual trusts. They induce possibilities and trigger optimism. They bear some barriers from the Eurocentric perspective of modernity and the mainstream literatures. All literatures matter. They should equally blossom and flourish. Indigenous literature has become an emerging discipline that upholds and strives for coexistence, interconnectedness, mutual respect and kinship.